2018
DOI: 10.1111/jvh.12929
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a hepatitis C clinical care coordination programme’s effect on treatment initiation and cure: A surveillance‐based propensity score matching approach

Abstract: Hepatitis C (HCV) is a viral infection that if left untreated can severely damage the liver. Project INSPIRE was a 3 year HCV care coordination programme in New York City (NYC) that aimed to address barriers to treatment initiation and cure by providing patients with supportive services and health promotion. We examined whether enrolment in Project INSPIRE was associated with differences in HCV treatment and cure compared with a demographically similar group not enrolled in the programme. INSPIRE participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…As such, it will be important to consider the implementation of evidence-based interventions that have been shown to enhance HCV testing [ 40 , 41 ], including medical chart reminders [ 40 ], dried-blood-spot testing [ 42 ], point-of-care HCV antibody testing [ 43 46 ], point-of-care HCV RNA testing [ 47 – 49 ], and reflex HCV RNA testing [ 50 52 ]. It will also be essential to implement strategies that have been demonstrated to increase treatment, including patient navigation or care coordination [ 53 55 ] and integration of HCV care into drug treatment settings [ 56 , 57 ]. Scale-up of evidence-based interventions to enhance HCV testing and treatment will be critical to achieve the increases in treatment uptake required to meet the WHO viral hepatitis elimination targets.…”
Section: Discussionmentioning
confidence: 99%
“…As such, it will be important to consider the implementation of evidence-based interventions that have been shown to enhance HCV testing [ 40 , 41 ], including medical chart reminders [ 40 ], dried-blood-spot testing [ 42 ], point-of-care HCV antibody testing [ 43 46 ], point-of-care HCV RNA testing [ 47 – 49 ], and reflex HCV RNA testing [ 50 52 ]. It will also be essential to implement strategies that have been demonstrated to increase treatment, including patient navigation or care coordination [ 53 55 ] and integration of HCV care into drug treatment settings [ 56 , 57 ]. Scale-up of evidence-based interventions to enhance HCV testing and treatment will be critical to achieve the increases in treatment uptake required to meet the WHO viral hepatitis elimination targets.…”
Section: Discussionmentioning
confidence: 99%
“…Participants enrolled had higher rates of HCV treatment initiation (72% vs. 36%) and cure (65% vs. 47%) than patients not enrolled in INSPIRE. 99 This model increased HCV provider capacity via telemedicine for primary care providers 100 and was found to cost very few resources--only 30 patients needed to be treated at each site to break even with budgetary expenses and the cost of the intervention totaled to less than $100 per month. 101,102 Increased funding to reimburse supportive services, ability to bill and reimburse for outpatient HCV care In the two-year period from November 2013-November 2015, during the transition from interferonbased treatment to interferon-free DAA regimens, researchers in NYC tested the impact of a multifacted intervention on rates of HCV screening among baby boomers in two primary care practices.…”
Section: Accepted Articlementioning
confidence: 99%
“…Participants enrolled had higher rates of HCV treatment initiation (72% vs. 36%) and cure (65% vs. 47%) than patients not enrolled in Project INSPIRE. (96) This model increased HCV provider capacity via telemedicine for primary care providers (97) and was found to cost very few resources (i.e., only 30 patients needed to be treated at each site to break even with budgetary expenses, and the cost of the intervention totaled to less than $100 per month). (98,99) Increased funding to reimburse supportive services, ability to bill and reimburse for outpatient HCV care in community-based settings, elimination of DAA restrictions, and innovative payer models could help lead to wider implementation of HCV care.…”
Section: Us Community-based Programsmentioning
confidence: 99%
“…As a demonstration project, INSPIRE was designed to monitor patient progress toward cure and evaluate treatment outcomes using clinical and care coordination data (9). Analysis of INSPIRE clinical outcomes has shown that participants enrolled in the program had better odds of initiating treatment and achieving SVR compared with similar HCV-infected individuals not enrolled in the program (10).…”
Section: Discussionmentioning
confidence: 99%